Wideband electromagnetic interference filtering power divider with a wide stopband using the genetic algorithm - Dai, Zhou; Li, Wei; Ma, Chenxin; Zhang, Wenfei; Tang, Wanchun (Frontiers in Physics, 2023)
This paper proposes a new design of electromagnetic interference wideband filtering power divider (FPD) with wide stopband based on genetic algorithm (GA). A set of data structures are constructed by describing corresponding the connection method between the basic units and their electrical parameters in the three-port design. Then GA is used to find the appropriate design topology and electrical parameters including isolation resistances to meet the FPD specifications by optimizing the data structures. For validation, one prototype is implemented. Results indicate that the new wideband FPD exhibits compact size, sharp roll-off, and good in-band isolations.